PENGARUH JUMLAH UANG BEREDAR DAN KURS TERHADAP TINGKAT INFLASI DI INDONESIA SEBELUM DAN SETELAH KRISIS GLOBAL 2009 - Hario Aji Hartomo (Lembaga Penerbit Fakultas Ekonomi dan Bisnis, 2010)
The objective of this research are to analyzed the effect of Money Supply and Exchange Rate to Inflation Rate in Indonesia before and after Global Crisis at 2008. Type of this research is a correlation study, a research to explain correlation between variables. Dependent Variable used is Inflation Rate (percentages), Independent Variables are Money Supply and Exchange Rate (Indonesian Rupiah to US Dollar). The models will be calculated with OLS (Ordinary Least Square) and Classical Assumption which is excelent in technical, easy to calculate and interpretation. In this case a correlation between dependent variables and independent variables. To determine the inflation rate effect before and after Global Crisis, the other test methods also needed, in example: Normality Test, Autocorrelation Test, Multicolinearity Test, Heteroscedastisity Test and Chow Test. The result from this research determine that Inflation Rate as a dependent variable will significantly influence to Money Supply and Exchange Rate inIndonesia.Keywords : global crisis, inflation rate, money supply